Application of Cooperative Learning Model Type Numbered Head Together (NHT) to Improve Students' Learning Outcomes on The Material of Appreciation of Historical Heritage at Mis Al-Hidayah School Namorambe - Harahap, Siti Rahmadani (Journal of Elementary School Education, 2024)
This study aims to improve students' learning outcomes in the material of appreciating historical heritage through the application of the Numbered Head Together (NHT) cooperative learning model at MIS Al-Hidayah Namorambe. The NHT learning model is one of the cooperative learning strategies that involves active participation of students in groups. In this process, each student is given a number and takes turns answering questions asked by the teacher. This approach aims to improve students' understanding, participation, and learning outcomes.The research method used is classroom action research (CAR) which is implemented in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. Data were collected through learning outcome tests and observation of student activities. The results of the study showed a significant increase in student learning outcomes after the implementation of the NHT model. In addition, the implementation of this model also increases learning motivation and cooperation between students in groups. The conclusion of this study is that the NHT type cooperative learning model is effective in improving student learning outcomes in the material of appreciating historical relics. Therefore, this model is recommended to be used as an alternative learning strategy in history subjects in elementary schools.